Antropologiczne ukierunkowanie mariologii kard. Stefana Wyszyńskiego - Bachanek, Grzegorz (Warszawskie Studia Teologiczne, 2017)
Cardinal Stefan Wyszyński portrays Virgin Mary as an example of a human being revived in Christ. It is a very specific example, which can be followed in the monastic life, in priesthood and in a family. Virgin Mary shows us the significance of a woman. She indicates how a woman may enrich the contemporary social life. Above all, however, she reminds us about the value of motherhood. She reveals the sense of human freedom. She teaches us how to love God with all one’s heart and how to serve brothers in a concrete and gentle manner. She shows us unity and the harmony of body and soul, the importance of a human body in God’s plan of salvation. The Marian piety favours the affective maturity of a human being, the gentleness and sensitivity towards others, the ability to combine emotions and re-ason in a mature way. It is in Virgin Mary that the author notices the sign of hope, particularly important for the human being of the twentieth century, devastated by the tragedy of war, and for a despairing sinner. Virgin Mary helps people discover the dignity of the child of God. She shows us the value of our everyday efforts. She reveals the future glory of the redeemed humanity.